Iteratively Developing an mHealth HIV Prevention Program for Sexual Minority Adolescent Men - Ybarra, Michele L. (AIDS Behav, 2016)
Five activities were implemented between November 2012 and June 2014 to develop an mHealth HIV prevention program for adolescent gay, bisexual, and queer men (AGBM): (1) focus groups to gather acceptability of the program components; (2) ongoing development of content; (3) Content Advisory Teams to confirm the tone, flow, and understandability of program content; (4) an internal team test to alpha test software functionality; and (5) a beta test to test the protocol and intervention messages. Findings suggest that AGBM preferred positive and friendly content that at the same time, did not try to sound like a peer. They deemed the number of daily text messages (i.e., 8–15 per day) to be acceptable. The Text Buddy component was well received but youth needed concrete direction about appropriate discussion topics. AGBM determined the self-safety assessment also was acceptable. Its feasible implementation in the beta test suggests that AGBM can actively self-determine their potential danger when participating in sexual health programs. Partnering with the target population in intervention development is critical to ensure that a salient final product and feasible protocol are created.